2008
DOI: 10.2174/1875039700801010087
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 and Flotillin-1 Differential Expression in Clinical Samples of Renal Cell Carcinoma

Abstract: Abstract:Caveolin-1 and flotillin-1 belong to plasma membrane microdomains. They are characterized by peculiar lipid and protein composition and are involved in fundamental cellular events such as: signal transduction, cell adhesion, lipid/protein sorting, and human cancer. We addressed caveolin-1 and flotillin-1 expression in 30 human renal cell carcinoma (RCC) and adjacent normal kidney (ANK) samples by SDS-PAGE and immunoblotting with specific antibodies. Significant caveolin-1 and flotillin-1 over-expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Regarding RCC, Raimondo’s membrane proteomic study suggested that FLOT1 was up-regulated in human RCC tissues compared to para-cancer kidney tissues [ 47 ]. However, until now, the function of FLOT1 in RCC has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding RCC, Raimondo’s membrane proteomic study suggested that FLOT1 was up-regulated in human RCC tissues compared to para-cancer kidney tissues [ 47 ]. However, until now, the function of FLOT1 in RCC has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…For one-dimensional electrophoresis (1-DE) Western blotting, 30 g of protein lysates, obtained from primary cell cultures and from renal tissue homogenate as described, 5,16 quantified with a Bio-Rad microassay (Hercules, CA), were separated on 10% SDS-PAGE and on NuPage 4 to 12% Bis-Tris pre-cast gels using MOPS SDS running buffer (Invitrogen), with described conditions. 5 For two-dimensional electrophoresis (2-DE) Western blotting, 50 g of proteins were loaded onto 7-cm 3-10 NL IPG-strips (GE Health care, Uppsala, Sweden) and then separated on NuPage 4% to 12% pre-cast gels.…”
Section: One-and Two-dimensional Electrophoresis and Western Blottingmentioning
confidence: 99%
“…Moreover, flotillin-1 functions as a regulatory signaling molecule that coordinates a variety of signal transduction processes. 14,15,21 Recent studies have revealed that flotillin-1 has important roles in the progression of several tumor types, including hepatocellular carcinoma, 22 neuroblastoma, 23 breast cancer, [24][25][26] tongue squamous cell cancer, 27 esophageal squamous cell carcinoma, [28][29][30] prostate cancer, 19 NSCLC, 5,31,32,33 renal cell carcinoma 34 and bladder transitional cell carcinoma. 35 Zhang SH et al have reported that a high level of flotillin-1 expression is associated with disease progression and poor prognosis in patients with hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%